Hemodynamic effects of IV sodium nitrite in hospitalized comatose survivors of out of hospital cardiac arrest - Dezfulian, Cameron (Resuscitation, 2017)
BACKGROUND: Patients resuscitated from cardiac arrest have brain and cardiac injury. Recent animal studies suggest that the administration of sodium nitrite after resuscitation from 12 minutes of asystole limits acute cardiac dysfunction and improves survival and neurologic outcomes. It has been hypothesized that low doses of IV sodium nitrite given during resuscitation of out of hospital cardiac arrest (OHCA) will improve survival. Low doses of sodium nitrite (e.g., 9.6 mg of sodium nitrite) are safe in healthy individuals, however the effect of nitrite on blood pressure in resuscitated cardiac arrest patients is unknown. METHODS: We performed a single-center, pilot trial of low dose sodium nitrite (1 or 9.6 mg dose) vs. placebo in hospitalized out-of-hospital cardiac arrest patient to determine whether nitrite administration reduced blood pressure and whether whole blood nitrite levels increased in response to nitrite administration. RESULTS: This is the first reported study of sodium nitrite in cardiac arrest patients. Infusion of low doses of sodium nitrite in comatose survivors of OHCA (n=7) compared to placebo (n=4) had no significant effects on heart rate within 30 minutes after infusion (70+ 20 vs. 78 ± 3 beats per minute, p=0.18), systolic blood pressure (103 ± 20 vs 108 ± 15 mmHg, p=0.3), or methemoglobin levels (0.92 ± 0.33 vs. 0.70 ± 0.26, p=0.45). Serum nitrite levels of 2–4 μM were achieved within 15 min of a 9.6 mg nitrite infusion. CONCLUSIONS: Low dose sodium nitrite does not cause significant hemodynamic effect in patients with OHCA, which suggests that nitrite can be delivered safely in this critically ill patient population. Higher doses of sodium nitrite are necessary in order to achieve target serum level of 10 μM.